2005
DOI: 10.1128/jb.187.17.6166-6174.2005
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Escherichia coli RNA Polymerase and Location of Binding Sites by Use of Chromatin Immunoprecipitation and Microarrays

Abstract: The genome-wide location of RNA polymerase binding sites was determined in Escherichia coli using chromatin immunoprecipitation and microarrays (chIP-chip). Cross-linked chromatin was isolated in triplicate from rifampin-treated cells, and DNA bound to RNA polymerase was precipitated with an antibody specific for the ␤ subunit. The DNA was amplified and hybridized to "tiled" oligonucleotide microarrays representing the whole genome at 25-bp resolution. RNA polymerase (RNAP) in Escherichia coli is a key factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(122 citation statements)
references
References 42 publications
9
111
0
2
Order By: Relevance
“…The differential RNAP-binding levels are defined as the difference between the sums of RNAP-binding levels across all probes in a targeted gene's ORF under the 2 conditions. In the previous report (14), there was very little correlation between the log 2 ratio of RNAP-binding peaks obtained from the rifampicintreated cells and the expression of the nearest downstream ORF. However, we observed that the changes in RNAP-binding levels are correlated with the changes in the mRNA transcript levels in response to the exogenous leucine (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The differential RNAP-binding levels are defined as the difference between the sums of RNAP-binding levels across all probes in a targeted gene's ORF under the 2 conditions. In the previous report (14), there was very little correlation between the log 2 ratio of RNAP-binding peaks obtained from the rifampicintreated cells and the expression of the nearest downstream ORF. However, we observed that the changes in RNAP-binding levels are correlated with the changes in the mRNA transcript levels in response to the exogenous leucine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the genome-wide Lrp-binding regions, we next performed a hybridization of the IP-DNA (Cy5 channel) and mock IP-DNA (Cy3 channel) onto the high-resolution whole-genome tiling microarrays, which contained a total of 371,034 oligonucleotides with 50-bp tiles overlapping every 25-bp on both forward and reverse strands (14). The normalized log 2 ratios obtained from the hybridization identify the genomic regions enriched in the IP-DNA sample compared with the mock IP-DNA sample and thereby represent a genome-wide map of in vivo interactions between Lrp protein and E. coli genome (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NimbleGen 60-mer arrays tiling over 36 Mb of the Drosophila genome at 100 bp resolution also have been used [39]. Binding by Escherichia coli TFs has been examined using off-the-shelf Affymetrix E. coli antisense arrays [40], while NimbleGen tiling arrays have been used to map E. coli RNA Pol binding sites [41].…”
Section: Chip-chipmentioning
confidence: 99%
“…Extensive efforts have recently been devoted to identifying the regulation target genes under the control of each TF by using highthroughput experimental systems such as the transcriptome and RNA-seq analyses of genome transcription patterns of TF-defective E. coli mutants (Cho et al, 2009;Raghavan et al, 2011;Ginnoukos et al, 2012) and upon exposure to stressful conditions such as changes in nutrients (Oh et al, 2002), exposure to heat shock (Richmond et al, 1999) or cold shock (Phadtare & Inouye, 2004), the presence of hydrogen peroxide (Zheng et al, 2001) or external metals (Lee et al, 2005), anaerobic conditions (Overton et al, 2006) and within biofilm (Ren et al, 2004). Direct measurement of TF-associated sites in vivo along the E. coli genome has been performed by ChIP-chip analysis (Herring et al, 2005;Grainger & Busby, 2008;Mooney et al, 2009). These in vivo analyses together provide information regarding TF-associated sites on the E. coli genome under the culture conditions employed, but are unable to identify the whole set of TF recognition sites because the functional forms of TFs are not always present in E. coli under laboratory culture conditions (see below) and because the TF-binding sites are often masked by other DNA-binding proteins.…”
Section: Introductionmentioning
confidence: 99%